Application Of Realistic Mathematics Education Approach With Concrete Materials To Improve Mathematics Learning Outcomes About Solid Figures For The Fifth Grade Students Of SDN Bangkal 01 In The Academic Year Of 2019/2020 - Rizky Indah Tri Wahyuni; Ngatman Ngatman; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The purposes of this study are: (1) describing the steps of applying the Realistic Mathematics Education approach with concrete materials, (2) improving mathematics learning outcomes about solid figures, and (3) describing the obstacles and solutions to the application of the Realistic Mathematics Education approach. This collaborative classroom action research was conducted in three cycles and six meetings. The research data are quantitative and qualitative data. Data collection techniques include observation, interviews and tests. The results of the study are: (1) the steps in the application of the Realistic Mathematics Education approach to improve Mathematics learning outcomes about solid figures are: a. understanding contextual problems through concrete materials, b. explaining contextual problems with concrete materials, c. resolving contextual problems with concrete materials, d. comparing, discussing, and answering question with concrete materials, and e. drawing conclusion; (2) the application of the Realistic Matematics Education approach can improve Mathematics learning outcomes about solid figures; (3) the obstacle in this study is students lack understanding to do worksheets, The solution is that the teacher asks the students concern to the instruction in worksheets.